Regeneration of Jaw Joint Cartilage in Adult Zebrafish - Smeeton, Joanna; Natarajan, Natasha; Anderson, Troy; Tseng, Kuo-Chang; Fabian, Peter; Crump, J. Gage (Frontiers in Cell and Developmental Biology, 2022)
The poor intrinsic repair capacity of mammalian joint cartilage likely contributes to the high incidence of arthritis worldwide. Adult zebrafish can regenerate many structures that show limited or no healing capacity in mammals, including the jawbone. To test whether zebrafish can also regenerate damaged joints, we developed a surgical injury model in which the zebrafish jaw joint is destabilized via transection of the major jaw joint ligament, the interopercularmandibular (IOP). Unilateral transection of the IOP ligament in one-year-old fish resulted in an initial reduction of jaw joint cartilage by 14 days, with full regeneration of joint cartilage by 28 days. Joint cartilage regeneration involves re-entry of articular chondrocytes into the cell cycle and upregulated expression of sox10, a marker of developing chondrocytes in the embryo that becomes restricted to a subset of joint chondrocytes in adults. Genetic ablation of these sox10-expressing chondrocytes shows that they are essential for joint cartilage regeneration. To uncover the potential source of new chondrocytes during joint regeneration, we performed single-cell RNA sequencing of the uninjured adult jaw joint and identified multiple skeletal, connective tissue, and fibroblast subtypes. In particular, we uncovered a joint-specific periosteal population expressing coch and grem1a, with jaw joint chondrocytes marked by grem1a expression during regeneration. Our findings demonstrate the capacity of zebrafish to regenerate adult joint cartilage and identify candidate cell types that can be tested for their roles in the regenerative response.